Nationalism's bloody terrain : racism, class inequality, and the politics of recognition - Baca, George (Critical interventions ;, 2006)
As many scholars have argued, racism and its passions are created by and subordinated to the nation. This volume places the practices of racism at the center of analysis of so-called post-racist or multi cultural nation-states. This way, each contributor analytically treats racism and its related concepts of race, identity, culture, and naturalizing symbols of blood to highlight the manner in which governing institutions use nationalist precepts to create "races". In the end, it is racism - the actual political practices of domination - that makes "race" salient, especially in its multi-cultural and liberal-democratic form.